Session 1, Panel 1, Williams, Michael. Storytelling, Peace and Conflict Resolution - Michael Williams - Jarvis, Dale (2010)
Michael Williams speaking at the 18th Annual Conference of Storytellers of Canada-Conteurs du Canada.